Regional practices in conducting sociolinguistic and monitoring research, as well as language forecasting and planning in the field of preservation and development of the native languages ​​of the peoples of Russia. - Lekhanov S. B. (Pedagogy, Psychology, Society: from theory to practice, 2024)
The article presents an overview of modern regional practices aimed at preserving and developing the native languages of the peoples of Russia. The concepts of ‘language forecasting’ and ‘language planning’ are revealed and the necessity of sociolinguistic and monitoring research is emphasized, the results of which can become the basis for formulating recommendations for public authorities, educational institutions and public organizations working in the field of language policy.
Keywords: родной язык; языковая политика; социолингвистические исследования; мониторинговые исследования; языковое прогнозирование; языковое планирование